2023
DOI: 10.3389/fimmu.2023.1203645
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus modulates mitochondrial dynamics, mitophagy, and mitochondria-derived vesicles to facilitate viral replication in trophoblast cells

Jae Kyung Lee,
Ok Sarah Shin

Abstract: Zika virus (ZIKV) remains a global public health threat with the potential risk of a future outbreak. Since viral infections are known to exploit mitochondria-mediated cellular processes, we investigated the effects of ZIKV infection in trophoblast cells in terms of the different mitochondrial quality control pathways that govern mitochondrial integrity and function. Here we demonstrate that ZIKV (PRVABC59) infection of JEG-3 trophoblast cells manipulates mitochondrial dynamics, mitophagy, and formation of mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Our data indicated that Drp-1-deficient MDBK cells upon NCP BVDV infection showed an elongated or enlarged mitochondrial morphology compared to NCP BVDV-infected cells alone (Figure 2 C). Previous studies have shown that mitochondrial fission induced by viral infection is important for virus propagation [ 32 , 33 ]. Thus, we speculate that the induction of mitochondrial fission is important for BVDV replication.…”
Section: Resultsmentioning
confidence: 99%
“…Our data indicated that Drp-1-deficient MDBK cells upon NCP BVDV infection showed an elongated or enlarged mitochondrial morphology compared to NCP BVDV-infected cells alone (Figure 2 C). Previous studies have shown that mitochondrial fission induced by viral infection is important for virus propagation [ 32 , 33 ]. Thus, we speculate that the induction of mitochondrial fission is important for BVDV replication.…”
Section: Resultsmentioning
confidence: 99%
“…The accumulating evidences suggest that viruses eliminate critical immune molecules within mitochondria by reducing mitochondrial mass to evade immune response (Mehrzadi et al, 2021; Wang et al, 2021a). For instance, the influenza A virus PB1-F2 protein degrades MAVS by triggering mitophagy (Wang et al, 2021b); coronaviruses, including SARS-CoV-2, promote their replication by altering mitochondrial dynamics and targeting MAVS (Mehrzadi et al, 2021; Shang et al, 2021); ZIKV NS4A induces mitochondrial fission and mitophagy to suppress MAVS-mediated IFN-I response (Lee and Shin, 2023); DENV disrupts mitochondrial biogenesis by downregulating the master regulators PPARγ and PGC1α (Singh et al, 2022). In our present study, we uncovered that ALSV NSP1 disrupts mitochondrial dynamics by reducing the levels of fission-related proteins, FIS1 and DRP1 to induce mitophagy, and inhibits mitochondrial biogenesis through suppressing the expression of PGC-1α, NRF1, and TFAM, ultimately resulting in a decrease in mitochondrial mass.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of ZIKV NS4A leads to mitochondrial fragmentation and inhibits the mitochondria-associated MAVS-mediated type I IFN response. 96 ZIKV infection significantly disrupts mitochondrial dynamics, inducing apoptosis through the activation of caspase-3, -9, -7, and poly (ADP-ribose) polymerase, which indicates the intrinsic apoptotic pathway is activated. This process includes the release of cytochrome c from the mitochondria and the aggregation of the apoptosis regulator BCL2-associated X on the outer OMM, occurring 48 h post-infection, which underscores ZIKV's role in the intrinsic apoptotic pathway.…”
Section: Zika Virusmentioning
confidence: 99%
“…The ZIKV NS4A translocates to the mitochondria, where it triggers mitochondrial fission and autophagy. Overexpression of ZIKV NS4A leads to mitochondrial fragmentation and inhibits the mitochondria‐associated MAVS‐mediated type I IFN response 96 . ZIKV infection significantly disrupts mitochondrial dynamics, inducing apoptosis through the activation of caspase‐3, ‐9, ‐7, and poly (ADP‐ribose) polymerase, which indicates the intrinsic apoptotic pathway is activated.…”
Section: The Viruses Accelerate Microglia Ageing Through Mitochondria...mentioning
confidence: 99%